Immunohistochemistry of Lymphocytes Subsets in Subclinical Experimental Paratuberculosis in Goats - Singh, U. M.; Tripathi, B. N.; Paliwal, O. P. (Nepalese Veterinary Journal, 2019)
The present experiment was carried out to find out the lymphocytes subsets reactions in experimentally induced subclinical paratuberculosis in goats. Twelve goats of 8-12 weeks age were infected with 4.23 x 109 Mycobacterium avium paratuberculosis on 8 occasions. Seven goats were kept as in-contact controls and 4 as uninfected controls. Immunohitochemistry for detection of cellular reaction of CD2+, CD4+, CD8+, CD25+, MHC I and MHCII in the lymphocytes present in the intestine and lymph node revealed more reactive cells in the infected goats as compared with the in-contact and infected control goats.